Location and quality service to satisfaction student Akademi Pariwisata Medan Hotel School - Rianto Manurung; Riza Afni; Susi Marta Tambunan; Haposan Hutahaen (Enrichment : Journal of Management, 2023)
Medan Hotel School Tourism Academy is one of the campuses that creates human resources in the field of tourism. This supports the Government's program to advance and develop the tourism industry that had been asleep. The satisfaction of students studying at the Medan Hotel School Tourism Academy will make this service business increasingly have a long life. This study used the help of SPSS as a data processor before drawing conclusions, with 35 students in semesters 4 and 6. The purpose of this study is to see whether the location of the campus and the services that have been provided by lecturers and employees have provided satisfaction to students. The method used in this study is quantitative by distributing questionnaires to students. The results of the answers are measured on the lIkert scale. The results of the study obtained that student satisfaction was obtained from the location of the campus location that is easily accessible to the community and located in a place that is often traversed by public transportation. It can be seen that location affects student satisfaction by t count > T table (4,078>2,036) Service also affects student satisfaction, where bad or good service will certainly have a direct impact on student satisfaction. The result of this study is that the location of the Medan Hotel School Parwisata Academy campus affects student satisfaction. Likewise, service also affects student satisfaction which is shown t Calculate > t table 6.357 > 2.036. Tested with Test F which obtained the result F count > F table (118.303 >3.28). which means that the conclusion, location and service simultaneously affect student satisfaction.